Electronic management as an entry to improve the quality of higher education institutions in Libya: A theoretical study of pioneering Arab and foreign experiences in this field - Mabruk , Salah; Al-Misrati, Salma (Journal of Pure & Applied Sciences, 2021)
“Electronic management” appeared which enabled some educational institutions to electronically process their documents that led to a decline in paperwork. Libyan institutions are needs to use electronic management to communicate with all their sub-systems and to ensure continuous interaction of all its components. The idea of this study was giving a perception of the concept of electronic management and the importance of its application in Libyan higher education institutions, leading to identifying the most important strategies that can be applied to achieve this quality. This study presented a theoretical framework by relying on the inductive and deductive approach, which includes analyzing the features of the current situation of electronic management and its role in improving the level of quality by presenting the most important Arab and foreign experiences in this field. The results of this study referred to the electronic management is a basic requirement in all countries that attempt to upgrade the educational system, in addition to the possibility of implementing all transactions electronically through the extensive use of information and communication technology. The study also recommended the necessity to get acquainted with the different experiences of electronic management and benefit from the results of their experiences, and what are the requirements and challenges of their using in terms of human and material resources and the electronic software industry, in addition to working on establishing a database in the Ministry of Higher Education and linking universities to it which provides a rapid exchange of information and access to it.